(untitled) (IPS Journal of Nutrition and Food Science, 2022)
Background: In developing countries, street vended foods continue to expand as an affordable food source which impacts the economy. However, the contamination of these foods leads to the outbreak of foodborne diseases and is considered a significant public health issue in Asian countries. This study assessed the microbial load and heavy metal contents in locally available street foods (shawarma, fruit chaat, and dahi baray) in different locations in Faisalabad city, Punjab province of Pakistan. Methods: A total of 60 food samples from five different locations in Faisalabad city were analyzed for microbial quality (Escherichia coli, Salmonella sp, and Staphylococcus aureus, and total viable count) and heavy metals levels (Zn, Cu, Pb, and Cd). A design was used to conduct questionnaires concerning vendors’ knowledge about food hygiene and sanitary practices. Data obtained were statistically analyzed by using the SPSS 21 Statistical Software. Results: The street foods were highly contaminated with Staphylococcus aureus (1.266×104 cfu g-1), Escherichia coli (0.370×104 cfu g-1), and Salmonella species (0.016×104 cfu g-1). The average heavy metal contamination of lead, zinc, copper, and cadmium were measured at 0.955 mg/kg, 3.712 mg/kg, 0.317 mg/kg, and 1.000 mg/kg, respectively. The survey questionnaire indicated the contamination of water and unhygienic conditions as significant sources of low-quality street foods. Conclusions: The results revealed that mostly the street foods sold in Faisalabad were contaminated with heavy metals and pathogenic bacteria. The unhygienic practices and contaminated water were the main factors for unhealthy street vended foods production. In this regard, food-safety practices, education, and regulations related to safe food production have been recognized as measures for ensuring the quality of vendor foods.